Search for the decay $B_s^0 → μ μ$ with the ATLAS detector - ATLAS collaboration (2869 authors) (2013)
A blind analysis searching for the decay Bs0 -> mumu has been performed using proton-proton collisions at a centre-of-mass energy of 7 TeV recorded with the ATLAS detector at the LHC. With an integrated luminosity of 2.4 fb^(-1) no excess of events over the background expectation is found and an upper limit is set on the branching fraction BR(Bs0 -> mu mu) < 2.2 (1.9) x10^(-8) at 95% (90%) confidence level.